Adherence to oral antineoplastic therapy - R. Olivera-Fernandez; F. Fernandez-Ribeiro; G. Piñeiro-Corrales; C. Crespo-Diz (Elsevier, 2014)
Background: Oral chemotherapy agents offer advantages including cost, patient comfort and potential improvement in quality of life versus intravenous drugs. However ensuring adherence and monitoring adverse effects is more difficult. The aim of this study was to examine the real adherence in patients with oral chemotherapy agents in our hospital, to assess the influence of patient and treatment characteristics, to identify reasons for non adherence, to identify pportunities for improvement pharmaceutical care and to assess the potential relation between adherence and treatment outcomes. Method: observational, prospective study for a period of four month, in the patients who were dispensing oral chemotherapy agents in outpatient setting. The medical prescriptions, medical history and patient interviews were used to collect data. Results: 141 patients were assessing. 72% were considered as fully adherent, while 28% reported some kind of non adherence. Adherence was influenced by time from diagnosis and adverse effects. No relationship between adherence and treatment outcomes was found. Conclusions: Adherence to oral chemotherapy was 72%, identifing opportunities for improvement pharmaceutical care to prevent adverse effects and to improve our patient adherence